Development of a Guideline to Assess Industrial Boiler Fuels for Sustainable Boiler Operations - Madhushani K Gunawardhana; Pradeep Gajanayake; Terancy P Samarawickrama; Dasuni T Bandaranayaka (Advances in Technology, 2025)
Industrial boilers play a significant role as a primary source of energy utilization in the industrial environment. In line with Sri Lanka’s Nationally Determined Contributions (NDCs) to reduce carbon emissions, significant actions include converting boiler energy sources to biomass and implementing guidelines to support the transition of industries into sustainable eco-industrial parks. Therefore, as energy sources, the selection of boiler fuel is significant to industries that consider sustainability and NDC actions. In the present study, sets of criteria were identified, and a guideline was formulated to assess industrial boiler fuels before starting the boiler operations for sustainable boiler practices in the Sri Lankan context associated with Seethawaka Export Processing Zone (SEPZ) using primary and secondary data sources. The resulting guideline consists of major boiler fuels, including biomass, coal, oil (diesel, heavy furnace oil and kerosene), processed waste (fabric) and electricity as an energy source. The guideline covers criteria related to fuel quality, maintenance practices, environmental regulations, issues related to fuels, fuel handling requirements, and environmental protection practices for each fuel relating to environmental, economic, and social sustainability. The guideline’s practical application was evaluated through a survey of industries at SEPZ. The survey results indicate that SEPZ industries meet the requirements of prepared guidelines by adhering to safety practices, holding necessary permits, and complying with environmental regulations, thus contributing to social sustainability. The SEPZ industries have achieved environmental sustainability by utilizing biomass as boiler fuel (49%), ensuring proper fuel storage, safe ash disposal, and dust arresting systems while maintaining compliance with environmental regulations. Additionally, economic sustainability has been attained through effective boiler maintenance, safety practices, and the widespread use of biomass. Also, awareness related to proper biomass is lower among industries. Thus, the guideline will lead to an increase in the awareness of boiler fuel usage in the industrial environment management sector.